Kualitas Perairan Situ Lebakwangi, Bogor - Jeanne Isbeanny; Syifa Annisa; Nurkholidah Nurkholidah; Nia Dzirwatul Izza; Pratiwi Amalia Zahrah; Dhiya Lathifah; Ario Putro Pamungkas; Nasti Susanti; Irawan Sugoro (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Water pollution that occurs due to various human activities in Situ Lebakwangi's cause of water quality decrease based on Government Regulation Number 82 of 2001 about Water Quality Criteria. The purpose of this research is to know the water quality of Situ Lebakwangi based on physical, chemical, and biological (coliform bacteria) factors. This research was conducted in Situ Lebakwangi, Bogor in January 2015. Physical factor parameters are temperature, dissolved oxygen (DO), pH, total dissolved solids (TDS), electrical conductivity (EC), five days of biological oxygen demand, brightness and light intensity. Research results show that the physical condition of Situ Lebakwangi is conformed with environmental quality standard class II.Temperature of Situ Lebakwangi range is 29,2-30,2 ˚C, DO 4,8-6,2 ppm, TDS 53,7-58,7 ppm, BOD5 1,6-3,1 ppm, EC 112-118 mS/cm, and pH 6,6-8,8. The measurement result shows that total bacteria exceed the environmental quality standard 1,0 x 103CFU/ml, except in the six-station. Pollutant bacteria E. coli was not found in the 6th station. All of the stations can not found pathogenic bacteria Salmonella sp. Coliform bacteria in five and six stations exceeds the environmental quality standard, which is 5,0 x 103. All observed physical factor parameters were in conformable with PP 82 of 2001 about Water Quality Criteria, but for biological parameters (total bacteria and total coliform) were not. Based on these results, aquatic of Situ Lebakwangi can not be used for water recreation facilities, freshwater fish cultivation, livestock, water to irrigate crops, and other uses that require the same water quality.